2016
DOI: 10.1371/journal.pone.0165565
|View full text |Cite
|
Sign up to set email alerts
|

Humanizing the Protease-Activated Receptor (PAR) Expression Profile in Mouse Platelets by Knocking PAR1 into the Par3 Locus Reveals PAR1 Expression Is Not Tolerated in Mouse Platelets

Abstract: Anti-platelet drugs are the mainstay of pharmacotherapy for heart attack and stroke prevention, yet improvements are continually sought. Thrombin is the most potent activator of platelets and targeting platelet thrombin receptors (protease-activated receptors; PARs) is an emerging anti-thrombotic approach. Humans express two PARs on their platelets–PAR1 and PAR4. The first PAR1 antagonist was recently approved for clinical use and PAR4 antagonists are in early clinical development. However, pre-clinical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Furthermore, an evaluation of the origin of circulating MP based on the presence of unique markers derived from parental cells revealed that microglial MP displayed the greatest increase (approximately twofold) following TBI, accounting for nearly 15% of total circulating MP. Although P2Y12 is also expressed on platelets [ 40 ], the detected P2Y12-positive MP were co-stained with CD45, a unique myeloid cell marker that is not expressed on platelets [ 41 , 42 ], indicating that the P2Y12-positive MP enriched in the circulation following TBI were not derived from platelets. These data indicate that microglial-derived MP are released by the TBI brain and reach the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an evaluation of the origin of circulating MP based on the presence of unique markers derived from parental cells revealed that microglial MP displayed the greatest increase (approximately twofold) following TBI, accounting for nearly 15% of total circulating MP. Although P2Y12 is also expressed on platelets [ 40 ], the detected P2Y12-positive MP were co-stained with CD45, a unique myeloid cell marker that is not expressed on platelets [ 41 , 42 ], indicating that the P2Y12-positive MP enriched in the circulation following TBI were not derived from platelets. These data indicate that microglial-derived MP are released by the TBI brain and reach the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Our findings are in contrast to endotoxemia models in PAR-1deficient mice, in which no effects on the LPS-induced inflammatory response or mortality were observed. 9 However, the profile of PAR expression in animals differs from humans, which may explain the differences in results, 10 but also the dose of endotoxin was several million-fold higher in the lethal mouse model (10 mg/kg vs. 2 ng/kg). The disagreeing results emphasize the importance of disease models performed in humans.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, the expression of PAR sub-types on cells differs relevantly between species. 10 Vorapaxar, a reversible, orally active, low-molecular weight, competitive antagonist of PAR-1 binds to the receptor with high affinity, inhibits thrombin-induced PAR-1 activation without affecting other platelet receptors and stops further intracellular signalling events. 11 Vorapaxar reduced the risk of experiencing major adverse cardiovascular events, while it also increased the bleeding rate in two phase III trials that included patients with non-ST-elevation myocardial infarction (MI) or patients with a history of MI, stroke or peripheral arterial disease.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, mice expressing human receptors have been generated. While this was successful in some cases (FcγRIIA) (194), other attempts failed so far to lead to functional receptor expression (PAR-1) (195, 196). However, the role of FcγRIIA was never addressed in a murine sepsis model.…”
Section: Rodent Models To Study the Role Of Platelets In Sepsismentioning
confidence: 99%